Analisis Perbandingan Model Respon Spektra Desain SNI 03-1726-2002, RSNI 2010 dan Metode PSHA - Suyadi . (UNIVERSITAS LAMPUNG, 2013)
Seismic load rules for the building as outlined in the SNI 03-1726-2002 which divided Indonesianarea in the 6 (six) earthquake regions. It is different to that in RSNI 03-1726-xxxx, which dividedIndonesia area > 6 the seismic zone. In addition earthquake time period use 500 years, while theRSNI 03-1726-xxxx uses 475 years and 2475 years earthquake time period. In the arrangement ofPeak Ground Acceleration values (PGA) is also used different attenuation formula’s in bothstandard. That's why research needs to be done to it by taking locations is Kalibalok intersection(Bandar Lampung) and Way Robok (West Lampung) as objects. The study focused on the shape ofthe response spectra design, in consideration seismic load can be analyzed with dynamic analysismethods which one with the response spectra. For add to the model, it was also use the methodPSHA calculations PGA for both locations. Based on the SPT test data that has been carried outby PT. Plato Isoiki, it turns out the two locations including the classification in stiff soil profile.Refer to result of the response spectra shape’s in both locations is different. At the Kalibalokmaximum value of acceleration response spectra if the design is made according to the results ofPSHA calculations with one sigma models. Whereas for area Robok Way maximum accelerationvalue is obtained if the design response spectra are arranged according RSNI-03-1726-xxxx. Thisis because when the earthquake time period, the attenuation function and seismic zoning isdifferent.